2023
DOI: 10.1177/23780231231217827
|View full text |Cite
|
Sign up to set email alerts
|

Aunties, Aunts, and Tías: The Forgotten Othermother Supporting and Housing LGBTQ Youth

Brandon Andrew Robinson,
Amy L. Stone,
Javania Michelle Webb

Abstract: Research on youth can miss important aspects of their lives if this work focuses only on the parent-child relationship. This focus can also overlook Black feminist interventions to understanding the roles of othermothers and can miss how nonparental relatives such as aunts may provide support, housing stability, and safety for youth. On the basis of a mixed-methods longitudinal study with 83 lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth in South Texas and the Inland Empire of California, the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Further, little is known about the role of non-parental relatives in the lives of sexual minorities, though recent interview research on gender and sexual minority youth has found that extended family members (i.e., aunts, uncles, cousins) often play a supportive role in their lives (Robinson et al, 2023;Stone et al, 2022). As the number of sexual minority grandparents increase (due to rises in the number of same-sex led families with children), more research will be needed to understand the effects of these relationships (Orel & Fruhauf, 2013).…”
Section: Linked Lives and Well-beingmentioning
confidence: 99%
“…Further, little is known about the role of non-parental relatives in the lives of sexual minorities, though recent interview research on gender and sexual minority youth has found that extended family members (i.e., aunts, uncles, cousins) often play a supportive role in their lives (Robinson et al, 2023;Stone et al, 2022). As the number of sexual minority grandparents increase (due to rises in the number of same-sex led families with children), more research will be needed to understand the effects of these relationships (Orel & Fruhauf, 2013).…”
Section: Linked Lives and Well-beingmentioning
confidence: 99%